Pendampingan Digitalisasi Layanan Kesehatan Hewan melalui Website Satwa Sehat di Petshop Karimata, Jember - Afrianto, Eko; Ayuningsih, Ekatri (Apik Cahaya Ilmu, 2025)
Digitizing animal health services is a crucial step in improving access and quality of care for pet owners. This research aims to assist the Karimata Petshop in Jember in developing a